Development, clinical presentation and endovascular management of congenital intracranial pial arteriovenous fistulas. (19th February 2012) - Paramasivam, Srinivasan; Toma, Naoki; Niimi, Yasunari; Berenstein, Alejandro
Abstract : Introduction: Pial arteriovenous fistulas (AVF) are vascular disorder of the brain consisting of a direct connection between arteries and veins without a nidus located in the subpial space, and are frequently associated with venous varix. Materials and Results: This study reviewed a series of 16 children with congenital pial AVF, treated between January 2005 and August 2011. All cases presented before 5 years of age and the mode of presentation varied with age. Fourteen had a single fistula while two had multiple fistulas, one among them had cutaneous features suggestive of RASA1 mutation. MRI is the preferred initial imaging, to demonstrate anatomical location, feeders, venous varix and regional, hemispheric or diffuse cerebralmalacia. Digital subtraction angiography performed during the first therapeutic attempt showed venous varix along with arterial enlargement as the most common angio-architecture. All cases were embolized with N-butyl-cyanoacrylate (NBCA) with or without coiling of the venous sac to attain flow control. Hypotension and a higher concentration of glue were used to aid controlled glue injections. Dural AVF and reactive angiogenesis are not uncommon sequlae found on follow-up angiogram. Outcomes were excellent in 75% and good in 19%. Conclusion: Congenital pial AVF are caused by a missed step in vascular development during the early embryonic stage. Transarterial endovascular embolizaiton using NBCA with or without using coils to attain flow control is the treatment of choice, with low morbidity. The efficacy of treatment is high as demonstrated by the high cure rate. Follow-up angiogram is mandatory to look for recanalization, reactive angiogenesis and denovo dural AVF development.